Flowers with style : the role of pollinators in the origin and maintenance of Proteaceae diversity with a focus on the genus Leucospermum - Johnson, Christopher Michael (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.